Combined Loss of Ghrelin Receptor and Cannabinoid CB1 Receptor in Mice Decreases Survival but does not Additively Reduce Body Weight or Eating. (1st November 2020) - Mani, Bharath K.; Castorena, Carlos M.; Vianna, Claudia R.; Lee, Charlotte E.; Metzger, Nathan P.; Vijayaraghavan, Prasanna; Osborne-Lawrence, Sherri; Elmquist, Joel K.; Zigman, Jeffrey M.
Highlights: Genetic deletion of GHSR does not exaggerate the reduced body weight, fat mass, or lean mass exhibited by mice lacking CB1R. Genetic deletion of both GHSR and CB1R in mice reduces survival. CB1R genetic deletion in ad libitum -fed mice does not affect plasma ghrelin. Application of cannabinoids to cultured gastric mucosal cells does not prominently affect ghrelin secretion. Abstract: Ghrelin administration increases food intake, body weight (BW), adiposity, and blood glucose. In contrast, although mouse models lacking ghrelin or its receptor (Growth Hormone Secretagogue Receptor (GHSR)) exhibit life-threatening hypoglycemia in starvation-like states, they do not exhibit appreciable reductions in food intake, BW, adiposity, blood glucose, or survival when food availability is unrestricted. This suggests the existence of a parallel neuromodulatory system that can compensate for disruptions in the ghrelin system in certain settings. Here, we hypothesized that the cannabinoid CB1 receptor (CB1R) may encode this putative redundancy, and as such, that genetic deletion of both GHSR and CB1R would exaggerate the metabolic deficits associated with deletion of GHSR alone. To test this hypothesis, we assessed food intake, BW, blood glucose, survival, and plasma acyl-ghrelin in ad libitum -fed male wild-type mice and those that genetically lack GHSR (GHSR-nulls), CB1R (CB1R-nulls), or both GHSR and CB1R (double-nulls). BW, fat mass, and lean mass were similar in GHSR-nulls and wild-types, lower in CB1R-nulls, but not further reduced in double-nulls. Food intake, plasma acyl-ghrelin, and blood glucose were similar among genotypes. Deletion of either GHSR or CB1R alone did not have a statistically-significant effect on survival, but double-nulls demonstrated a statistical trend towards decreased survival ( p = 0.07). We conclude that CB1R is not responsible for the normal BW, adiposity, food intake, and blood glucose observed in GHSR-null mice in the setting of unrestricted food availability. Nor is CB1R required for plasma acyl-ghrelin secretion in that setting. However, GHSR may be protective against exaggerated mortality associated with CB1R deletion.